Adsorption and movement of water by skin of the Australian thorny devil (Agamidae: Moloch horridus). Issue 9 (13th September 2017) - Comanns, Philipp; Esser, Falk J.; Kappel, Peter H.; Baumgartner, Werner; Shaw, Jeremy; Withers, Philip C.
Abstract : Moisture-harvesting lizards, such as the Australian thorny devil Moloch horridus, have remarkable adaptations for inhabiting arid regions. Their microstructured skin surface, with channels in between overlapping scales, enables them to collect water by capillarity and passively transport it to the mouth for ingestion. We characterized this capillary water transport for live thorny devils using high-speed video analyses. Comparison with preserved specimens showed that live lizards are required for detailed studies of skin water transport. For thorny devils, there was no directionality in cutaneous water transport (unlike Phrynosoma ) as 7 µl water droplets applied to the skin were transported radially over more than 9.2 mm. We calculated the total capillary volume as 5.76 µl cm −2 (dorsal) and 4.45 µl cm −2 (ventral), which is reduced to 50% filling by the time transportation ceases. Using micro-computed tomography and scanning electron microscopy of shed skin to investigate capillary morphology, we found that the channels are hierarchically structured as a large channel between the scales that is sub-divided by protrusions into smaller sub-capillaries. The large channel quickly absorbs water whereas the sub-capillary structure extends the transport distance by about 39% and potentially reduces the water volume required for drinking. An adapted dynamics function, which closely reflects the channel morphology, includes that ecological role.